2020
DOI: 10.1371/journal.pbio.3000792
|View full text |Cite
|
Sign up to set email alerts
|

Heritable gene expression variability and stochasticity govern clonal heterogeneity in circadian period

Abstract: A ubiquitous feature of the circadian clock across life forms is its organization as a network of cellular oscillators, with individual cellular oscillators within the network often exhibiting considerable heterogeneity in their intrinsic periods. The interaction of coupling and heterogeneity in circadian clock networks is hypothesized to influence clock's entrainability, but our knowledge of mechanisms governing period heterogeneity within circadian clock networks remains largely elusive. In this study, we ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 94 publications
2
20
0
Order By: Relevance
“…The center panel depicts the same collection of curves but with the vertical axis scaled proportionally to the panel on the right, which shows a summation of the individual profiles shown to the left. This simply derived additive curve resembles, e.g., bioluminescence profiles showing clock regulated gene expression, such as shown in Nikhil and colleagues [4]. Actual expression curves should vary according to what is quantified-they could be broader or narrower depending on what is measured and on the distribution of component entrained phases.…”
Section: The Phase-period Rulementioning
confidence: 72%
See 3 more Smart Citations
“…The center panel depicts the same collection of curves but with the vertical axis scaled proportionally to the panel on the right, which shows a summation of the individual profiles shown to the left. This simply derived additive curve resembles, e.g., bioluminescence profiles showing clock regulated gene expression, such as shown in Nikhil and colleagues [4]. Actual expression curves should vary according to what is quantified-they could be broader or narrower depending on what is measured and on the distribution of component entrained phases.…”
Section: The Phase-period Rulementioning
confidence: 72%
“…A longer free-running rhythm usually leads to a later entrained phase relative to a shorter one. This has been shown on various levels, demonstrating the pervasiveness of the principles of circadian biology: not only do whole organisms show these properties, but so do the organs and cells within them [3,4].…”
Section: Box 2 Circadian Organizationmentioning
confidence: 98%
See 2 more Smart Citations
“…Notably, this cluster corresponded to the observed high frequency of Ca 2+ spike, and might therefore represent SCN neuronal activity. To analyze which transcripts exerted the most significant influence on PC1 in this model, we used the cos 2 values to scale their relative importance (Nikhil et al, 2020). We shortlisted the top 214 genes that meet cos 2 > 0.5, and interestingly found that 142 genes among 214 genes had significantly different expression in the ZT0-4 TRF entrained SCN at CT1 samples compared with other groups (See detailed in methods).…”
Section: Resultsmentioning
confidence: 99%